2010
DOI: 10.1016/j.jtcvs.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary proteomics before and after extracorporeal circulation in patients with and without acute kidney injury

Abstract: Cardiopulmonary bypass leads to increased urinary excretion of inflammatory proteins and markers of tubular injury. Zinc-alpha-2-glycoprotein is a potentially useful predictive marker for acute kidney injury after cardiopulmonary bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…It is elevated in urine during energy-demanding conditions (15), but decreases in acute kidney injury (16). However, on individual quantification in the validation set, ZAG levels were similar to those found in patients with FSGS-unrelated proteinuria, thus lacking the specific link to FSGS.…”
Section: Discussionmentioning
confidence: 72%
“…It is elevated in urine during energy-demanding conditions (15), but decreases in acute kidney injury (16). However, on individual quantification in the validation set, ZAG levels were similar to those found in patients with FSGS-unrelated proteinuria, thus lacking the specific link to FSGS.…”
Section: Discussionmentioning
confidence: 72%
“…111 Aregger and collegues examined the urinary proteome of 36 adults undergoing CPB. 112 In the 6 patients that developed AKI, defined by RIFLE criteria, urinary albumin was increased, and zinc-alpha-2-glycoprotein and a fragment of adrenomedullin-binding protein were decreased. Most recently, Heller and colleagues have shown that urinary calprotectin, an activator of the innate immune system, reliably differentiates pre-renal azotemia from intrinsic AKI in a group of hospitalized patients, supporting the predictive role of the urinary proteome even in heterogeneous patient populations.…”
Section: Protein Biomarkers Of Akimentioning
confidence: 96%
“…Although these are small studies, they suggest that the excretion of this protein is decreased during AKI. Further proteomic studies are needed to determine whether a decrease in urinary uromodulin would be a suitable biomarker for AKI 82 . Could the baseline rate of urinary uromodulin excretion be predictive of susceptibility to AKI?…”
Section: Recent Advancesmentioning
confidence: 99%